Kinetically stable metal ligand charge transfer complexes as crosslinks in nanogels/hydrogels: Physical properties and cytotoxicity. (15th October 2015) - Wang, Rong; Both, Sanne K.; Geven, Mike; Calucci, Lucia; Forte, Claudia; Dijkstra, Pieter J.; Karperien, Marcel
Graphical abstract: Abstract: A terpyridine end-functionalized 8-arm poly(ethylene glycol) was prepared using the reaction of a 4′-aminopentanoxy substituted terpyridine with a p-nitrophenyl chloroformate activated PEG-(OH)8 . Supramolecular complexation of the polymer terpyridine moieties by Fe 2+ ions was investigated using NMR, UV–Vis and dynamic light scattering experiments. At low concentrations addition of Fe 2+ ions to an aqueous solution of the polymer conjugate afforded nanogels with a single size distribution around 250 nm. At concentrations above 3 wt%, and at a 1:2 metal to ligand molar ratio, hydrogels were formed with increasing mechanical properties at increasing polymer concentrations. Using bovine chondrocytes, the biocompatibility and potential cytotoxicity of the polymer conjugate, nanogels and hydrogels were studied. The polymer conjugate with free ligands was toxic to the cells likely due to depletion of essential metal ions. When the terpyridine groups were complexed with Fe 2+ ions, both nanogel suspensions and hydrogels showed no cytotoxicity in direct contact with chondrocytes. Indirect contact of gels with chondrocytes using transwells revealed the absence of toxic components by leaching. A Live-Dead assay on chondrocytes encapsulated in the hydrogels indicated that the hydrogels are cytocompatible, revealing the potential use of these materials for biomedical and pharmaceutical applications. Statement of Significance: The binding between transition metal ions and ligands with multiple binding sites can be almost as strong as covalent bonds. This metal–ligand charge transfer (MLCT) complexation was used to crosslink water soluble polymers into hydrogels. This approach to novel materials may find applications in the biomedical and pharmaceutical fields. Transition metal ions are essential trace elements present in tissue but up to now no cytotoxicity data of free ligands are available. Data presented show that free ligands are toxic to cells likely by depletion of trace metal ions, whereas kinetically stable complexes are not cytotoxic even when embedded in hydrogels. These results provide fundamental issues to be considered in the design of hydrogels crosslinked through metal ligand complexation.